الحد الادنى من الخدمة في قانون العمل - برتيمة, عبد الوهاب (revue mofakir; No 09 (2013): مجلـــة المفكــر, 2018)
تظهر أهمية الدراسة حول التوفيق والتناسب بين الحق الخاص – الحق في الإضراب – ،والمصلحة العامة المتوخاة من استمرارية المرفق العام ، والبحث عن ضمان التوازن بين الحق والمصلحة ، وهل يجد هذا التوافق الصعب والضروري حله في إيجاد مقاييس الحد الأدنى من الخدمة ، والدراسة حاولت إعطاء مفهوم الحد الأدنى من الخدمة ، وكيفية ضمان وتفعيل ،وإعمال هذا الحد الأدنى من الخدمة أثناء الإضراب ، ضماناً لسيرورة المرفق العام . Abstract : The present study deals with the reconciliation of the right to strike and public interest in the continuity of public utilities. It also inquires the balance between the right and the interest and whether this difficult and necessary reconciliation can contribute to setting minimum service criteria. The study attempts to give a definition to the concept of minimum service and the way it can be assured and made operational during the strike for public utilities sake.